Zakat Fitrah dan Nasab Anak: Kritik atas Penelantaran Hak-Hak Anak dalam Keluarga Muslim dalam Perspektif Pendidikan Agama Islam - Andrini, Mike; Kartika, Novita Erni; Erlina; Ghazi, Fachrul; Kholid, Idham (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The social phenomenon within contemporary Muslim communities indicates that many families still neglect children’s fundamental rights, including education, financial support, and emotional care. This condition reflects a gap between the ideal values of Islamic teachings and their practical implementation in family life. This study aims to critically examine the interrelation between zakat fitrah (alms of purification), lineage (nasab), and the fulfillment of children’s rights from the perspective of Islamic Religious Education. Employing a qualitative approach with a library research design, this study applies content analysis to primary sources such as the Qur’an, Hadith, classical works of tafsir and fiqh, as well as secondary data from academic books, journals, and previous studies. The findings reveal that zakat fitrah possesses profound spiritual and social dimensions. It functions not only as an act of ritual purification but also as an instrument of social education that cultivates justice, empathy, and collective responsibility. Meanwhile, the concept of nasab serves as a moral and educational foundation within the family, emphasizing parental responsibility to fulfill children’s rights to love, protection, and moral guidance. The lack of understanding of these two concepts has weakened the family’s role as a moral and spiritual educational institution. Therefore, integrating the values of zakat fitrah and nasab into Islamic Religious Education is essential for developing a family-based educational paradigm grounded in raḥmah (compassion), ‘adl (justice), and amānah (responsibility).